Can race really be erased? A pre-registered replication study - Voorspoels, Wouter; Bartlema, Annelies; Vanpaemel, Wolf (Frontiers in Psychology, 2014)
When encountering an unknown individual, social categorization of the individual has been shown to automatically proceed on the basis of three fundamental dimensions: People seem to mandatorily encode race, sex and age. In contradiction to this general finding, \citeA{Kurzbanetal2001} showed that race encoding is not automatic and inevitable, but rather a byproduct of categorization in terms of coalitions. In particular, they argue and empirically support that when other coalitional information is present, the encoding of race is spectacularly reduced. In the present contribution, we present a replication of the race-erased effect reported by Kurzban et. al. First, we give a detailed overview of the hypotheses, the experimental methodology, the derivation of the sample size required to achieve a power of 95%, and the criteria that need to be met for a successful replication. Then we present the findings of an empirical test that met the requirements of our power analyses. Our results indicate that the encoding of race can indeed be reduced when another coalitional cue is available, yet this reduction is less marked than in the original study. This experiment was preregistered before data collection at Open Science Framework, osf.io/vnhrm/.